PENGGUNAAN STRATEGI PENERJEMAHAN KOSAKATA BUDAYA JAWA TENGAH BERBAHASA INDONESIA KE DALAM BAHASA JEPANG DALAM MEDIA INFORMASI PARIWISATA - Sri Muryati; Bekti Setio Astuti (Jurnal CULTURE (Culture, Language, and Literature Review), 2020)
This research is a study on cultural word translation strategies from Indonesian into Japanese. The purposes of the study are: firstly, identifying cultural words that do not have any equivalence between the source language (TSu) secondly, investigating the translation strategies used for those words with no equivalence; and thirdly, finding out the meaning shift occurring in the process of translation. The research employs a descriptive qualitative method. The strategies used by the translator include: 1) translation using more general terms, 2) translation using loan words or loan words with explanation, 3) translation using paraphrase. Two meaning shifts are found: 1) shift from generic to more specific or vice versa, and 2) shift because of different cultural point of view.